2013
DOI: 10.4103/0970-1591.109988
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of iatrogenic bladder perforation during transurethral bladder tumor resection: Case report and literature review

Abstract: An intraperitoneal bladder perforation occurred during transurethral tumor resection under general anesthesia in a 82 year old woman. The bladder was repaired with a laparoscopic closure and an indwelling urethral catheter. The histopathology revealed T1 high grade urothelial carcinoma. The patient recovered well and was discharged home on postoperative day 7. This case highlights the successful use of laparoscopy in the treatment of a rare urological complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Patients with extraperitoneal perforations are managed with surgery repaired for the perforation and the bowel. Recent studies have reported that intraperitoneal bladder perforations can be treated with minimally invasive approaches, such as laparoscopic repair or percutaneous peritoneal drainage [12 , 13] . In addition, the treatment of complications, such as hyperkalemia, acidosis, and sepsis, play essential roles [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with extraperitoneal perforations are managed with surgery repaired for the perforation and the bowel. Recent studies have reported that intraperitoneal bladder perforations can be treated with minimally invasive approaches, such as laparoscopic repair or percutaneous peritoneal drainage [12 , 13] . In addition, the treatment of complications, such as hyperkalemia, acidosis, and sepsis, play essential roles [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic repair of iatrogenic intraperitoneal bladder perforation has previously been reported as a more conservative alternative to open laparotomy. 7,8 Passing the resectoscope through the perforation and using this to guide the percutaneous placement of a pigtail drain has also been described. 9 We would like to present a case in which a small 20F zero degree urethroscope was passed through a perforation created during TURBT to inspect the adjacent bowel for possible injury and to avoid an open laparotomy.…”
Section: Introductionmentioning
confidence: 99%